Konsentrasi Anion Di Udara Ambien Dan Analisis Lintasan Balik Sumber Polutan Di Kota Semarang - Haryono S Huboyo; Mochtar Hadiwidodo; Mochamad Nurihsan (Jurnal Serambi Engineering, 2020)
Air pollution in urban areas shows fluctuations in quality due to increasingly complex pollutant sources. This study aimed to determine the content of water soluble anions and sources of dust pollutants using the back trajectory method. Air quality dust was taken at the end of 2019 in Pedurungan District and Gunungpati District in Semarang City for 2 days with a dust measuring device at each sample point. From each sample, a laboratory test was carried out on its anion content. Anions were analyzed at the Diponegoro University Integrated Laboratory by ion chromatography. The dust concentration ranges from 60 - 90 µg/Nm3 with anion content below 25%. Some of the dominant anions are thought to come from industrial activities such as burning coal and densely populated areas in the city of Semarang. Based on the results of the trace back from the origin of the dust, it can be seen that the dust comes from the south area (Genuk area). Therefore, air pollution mitigation is directed to the South, where the potential comes from industrial activities and vehicles.